Adaptive backpropagation neural network in system protection scheme - Azriyenni, Azriyenni (2013)
This paper proposes technique of backpropagation neural network in power system protection scheme. The main objective this paper is perform protection system model to transmission line using technique Backpropagation Neural Networks. An improvement in performance to distance relay is expected after the backpropagation could acquire with different fault conditions. The implemented Backpropagation Neural Network should catch knowledge for the correct distance relay operation in appearance the different network conditions. In power system of three phase currents and voltages at fault location are used as inputs to Backpropagation Neural Network based on power system protection scheme. The Backpropagation Neural Networks are trained to address fault location. The reliability of proposed scheme investigated which using power system in transmission line by using Matlab.